Selective Hydrogenation of Polyunsaturated Fatty Acid Methyl Esters over Bifunctional Ligand-Modified Pd/MIL-101(Cr) Catalysts - Phuwadon Khenkhom; Chonlada Ritvirulh; Kittisak Choojun; Yardthip Preedawichitkun; Narong Chanlek; Tawan Sooknoi (Inorganic Chemistry, 2025)
formation, reducing activity. Hot filtration and recyclability tests confirmed high catalyst stability and negligible Pd leaching. The bifunctional ligand architecture effectively tunes Pd speciation and activity, providing a robust platform for selective and reusable hydrogenation catalysts.
Keywords: Catalysis for Biomass Conversion; Catalysis and Hydrodesulfurization Studies; Asymmetric Hydrogenation and Catalysis